GUT and Flavor Models for Neutrino Masses and Mixing - Meloni, Davide (Frontiers in Physics, 2017)
In the recent years neutrino experiments have studied in detail the phenomenon of neutrino oscillations and most of the oscillation parameters have been measured with a good accuracy. However, in spite of many interesting ideas, the problem of flavor in the lepton sector remains an open issue. In this review, we discuss the state of the art of models for neutrino masses and mixing formulated in the context of flavor symmetries, with particular emphasis on the role played by grand unified gauge groups.